Accident analysis to support the development of strategies for the prevention of brain injuries in car crashes. (August 2018) - Antona-Makoshi, Jacobo; Mikami, Koji; Lindkvist, Mats; Davidsson, Johan; Schick, Sylvia
Highlights: Estimation of brain injury frequencies and risks for occupants of modern car crashes in the US. Concussions comprise 79% of all AIS2+ brain injuries. Belted women are more likely to sustain concussions than men. Elderly are more likely to sustain Subdural Haemorrhages than non-elderly. Abstract: This study estimated the frequency and risk of Moderate -to- Maximal traumatic brain injuries sustained by occupants in motor vehicle crashes in the US. National Automotive Sampling System - Crashworthiness Data System crashes that occurred in years 2001–2015 with light vehicles produced 2001 or later were incorporated in the study. Crash type, crash severity, car model year, belt usage and occupant age and sex were controlled for in the analysis. The results showed that Moderate concussions account for 79% of all MAISbrain 2+ injuries. Belted occupants were at lower risks than unbelted occupants for most brain injury categories, including concussions. After controlling for the effects of age and crash severity, belted female occupants involved in frontal crashes were estimated to be 1.5 times more likely to sustain a concussion than male occupants in similar conditions. Belted elderly occupants were found to be at 10.5 and 8 times higher risks for sub-dural haemorrhages than non-elderly belted occupants in frontal and side crashes, respectively. Adopted occupant protection strategies appear to be insufficient to achieve significant decreases in risk of both life-threatening brain injuries and concussions for all car occupants. Further effort to develop occupant and injury specific strategies for the prevention of brain injuries are needed. This study suggests that these strategies may consider prioritization of life-threatening brain vasculature injuries, particularly in elderly occupants, and concussion injuries, particularly in female occupants.